Implementasi Kebijakan Pengembangan Kompetensi berbasis E-learning melalui Program Flexible Micro Learning di Instansi Pemerintah - Widaningsih Widaningsih (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2026)
This study analyses the implementation of e-learning-based competency development policy at the Center for Learning and Policy Strategy for National Civil Service Talent, National Institute of Public Administration through the Flexible Micro Learning (FML) program. The research employs a descriptive quantitative approach using Edwards III's policy implementation model, which encompasses communication, resources, disposition, and bureaucratic structure dimensions. Data were collected from 54 civil servants participating in the FML program through questionnaires and structured interviews. The findings indicate that policy implementation falls into the "good" category with an overall score of 86.87%. The resources dimension obtained the highest score (87.70%), followed by communication (87.00%), disposition (86.88%), and bureaucratic structure (84.41%). However, several obstacles were identified, including time limitations, a shortage of specialised human resources (Instructional Technology Developers), budget constraints, and the absence of detailed operational standards. Through SWOT analysis, this study formulates four strategic recommendations: strengthening external collaboration, developing human resource collaboration strategies, mitigating policy and technical risks, and conducting regular consultations with stakeholders.